The infrared and molecular environment surrounding the Wolf-Rayet star WR 130 - Cichowolski, Silvina (2015)
We present a study of the molecular CO gas and mid/far-infrared radiation arising from the environment surrounding the Wolf-Rayet (WR) star 130. We use the multiwavelength data to analyse the properties of the dense gas and dust, and its possible spatial correlation with that of young stellar objects (YSOs). We use 12CO J=1-0 data from the Five College Radio Astronomy Observatory survey as tracer of the molecular gas, and mid/far-infrared data from the recent Wide-Field Infrared Survey Explorer (WISE) and Herschel space surveys to study the dust continuum radiation and to identify a population of associated candidate YSOs. The spatial distribution of the molecular gas shows a ring-like structure very similar to that observed in the H I gas, and over the same velocity interval. The relative spatial distribution of the H I and CO components is consistent with a photodissociation region. We have identified and characterized four main and distinct molecular clouds that create this structure. Cold dust is coincident with the dense gas shown in the CO measurements. We have found several young stellar object candidates that lie along the regions with the highest gas column density, and suggest that they are spatially correlated with the shell. These are indicative of regions of star formation induced by the strong wind and ionization of the WR star.